Exploring health professionals´ experiences of being involved in a research project. Issue 2 (3rd April 2021) - Laustsen, Christine E.; Petersson, Pia; Westergren, Albert; Haak, Maria
ABSTRACT: The involvement of health professionals in research may ensure the acquisition of relevant and sustainable knowledge that is applicable in practice. However, knowledge is lacking about how professionals experience being involved. Therefore, the aim of this study was to explore how health professionals experienced the process of being involved in a project related to research on ageing and health. Data was collected through seventeen interviews and analysed using a grounded theory approach. The findings illustrate the health professionals' experiences of an adaptation process that occurred, e.g., adapting practice and research to facilitate collaboration and the ability to co-create. Influenced by circumstances and through ongoing negotiations and breakthroughs, co-creation was experienced, based on the health professionals' and researchers' trustful relationships. In conclusion, this new knowledge may be useful in designing and implementing future studies that involve health professionals in research projects on ageing and health.